'Ruffled' Mistresses and 'Discontented' Maids: Respectability and the Case of Domestic Service, 1880-1914 - Fahrni, Magda (Labour / Le Travail, 1997)
Domestic service was an institution of considerable importance for working-class women and middle-class householders in Canada between 1880 and 1914. Service was instrumental in shaping class relations, in large part because it brought the working class directly into the bourgeois home. It was thus an arena where bourgeois and working-class versions of respectability met, and sometimes clashed. Service was essential to the elaboration of a respectable bourgeois lifestyle, and was considered a satiable occupation for working women, yet the peculiar restrictions of the occupation ensured that domestics would often find the trappings of respectability difficult to maintain. Domestics walked a fine line between 'respectability' and 'deviance'; indeed, in the eyes of many, service was an institution that straddled this line.
Keywords: Canada; HOUSEHOLD employees; LIFESTYLES; Stockholders; Women employees; Working class